Time trend and clinical pattern of extrapulmonary tuberculosis in Serbia, 1993-2007 - Pešut Dragica P.; Bulajić Milica V.; Lešić Aleksandar R. (Vojnosanitetski Pregled)
Background/Aim. Increased incidence of extrapulmonary tuberculosis (XPTB) is reported worldwide. Serbia is a country in socio-economic transition period with lowmiddle HIV prevalence and intermediate-to-low tuberculosis (TB) incidence rate, 100% directly observed treatment (DOT) coverage, and mandatory BCG vaccination at birth. The aim of the study was to examine the incidence trend and clinical features of XPTB in Serbia during a 15-year period. Methods. This retrospective observational study included XPTB cases diagnosed in the period between 1st January 1993 and 31st Decembre 2007, according to the reports of the National Referral Institute of Lung Diseases and Tuberculosis in Belgrade and Central Tuberculosis Register. Population estimates with extrapolations were based on 1991 and 2002 census data. Results. While the overall TB incidence rate showed a slight, not significant decreasing trend (p = 0.535), a significant increase was found for XPTB (y = 1.7996 + 0.089x; R2 = 0.4141; p = 0.01). A total of 2,858 XPTB cases (newly diagnosed and 10% relapses) gave an average age specific incidence rate of 2.51/100,000 population (95% confidence interval, SD = 0.6182) with 8.9% annual increase. The male-to-female ratio was 0.54. Lymph nodes were most frequently affected site (48.5%) followed by genitourinary (20.5%), pleural (12%), and osseo-arthicular (10.3%) TB. Treatment outcome was successful in 88.29% of patients (cured and completed), 3.64% died, 5.18% interrupted, 0.57% displaced, and 2.3% unknown. Conclusion. Increasing trend of XPTB incidence rate may be a result of increased morbidity due to still present risk factors, possible higher detection rate in Serbia and better notification. A high coverage of newborns with BCG vaccination at birth might contribute to a decreased number and rare XPTB cases in children.